Pengaruh Model Pembelajaran Inquiry Based Learning Terhadap Kemampuan Scientific Reasoning Pada Mata Pelajaran IPA di Kelas V SDIT Wasilatul Huda - Nurmatin, Suci; Nuri Nurul Aini (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2024)
This research is based on the low scientific reasoning ability of students, this can be seen from the lack of student test results, especially in science subjects in class V. Apart from that, based on data from the Organization for Economic Co-Operation and Development (OECD), the test results Based on the Program for International Student Assessment (PISA) in 2018 which tested reading, mathematics and science abilities, Indonesia was ranked 72nd out of 77 countries. Indonesia's PISA average score has decreased across all competencies. Specifically for science competency, the average score decreased from 403 in 2015 to 396 in 2018, this figure is below the OECD average of 4898. The low value of science competency also shows that the scientific reasoning abilities of students in Indonesia are low. Scientific reasoning or scientific reasoning is the ability to think systematically and logically which aims to solve problems using scientific methods including the stages of evaluating facts, making predictions and hypotheses, determining and controlling variables, designing and conducting experiments, collecting data, analyzing data and drawing conclusions. From these problems, the problem that will be researched is the influence of the Inquiry-Based Learning learning model on students' Scientific Reasoning abilities. This research is a Quasi Experiment using One Group Time Series Design. The population in this study was 146 students from grades 1 to V at SDIT Wasilatul Huda. The core research sample consists of one class, namely class V. The data collection instrument is a multiple choice test consisting of 25 questions which was developed based on the Lawson Classroom Test Scientific Reasoning (LCTSR) and field observations in the form of interviews. Based on the research that has been carried out, data has been obtained which shows that there is an influence of the use of the Inquiry-Based Learning learning model on students' Scientific Reasoning abilities. This is indicated by the significant results obtained at 0.000, which means sig<0.05 so that H1 is accepted. Based on these results, it is proven that the Inquiry-Based Learning learning model has an effect on students' Scientific Reasoning abilities